فسخ نکاح بذریعہ عدالت سے متعلق مسائل :ائمہ اربعہ اورمولاناسیدابوالاعلیٰ مودودیؒ کا تجزیاتی مطالعہ: Legal Aspects of Marriage Dissolution in Court: A Comparative Study of the Four Imams and Maulana Sayyid Abul A'la Maududi's Positions - Rabia Hina,; Sadeeq Ahmad,; Asghar Inam, (Al Manhal Research Journal, 2023)
Islamic jurisprudence includes specific rules about marriage and divorce. These commandments can be found in the Quran, Sunnah (Prophet Muhammad's teachings and practices), and historical sources. These sources contain information on the specifics, laws, and examples of marriage and divorce. Marriage and divorce are serious and complex topics, so the final decision rests with the court for explanation and settlement. The court also bases its judgements on the Quran and Sunnah. Because the court is a powerful institution in the country, disobeying its decisions is not permitted. The court will make choices regarding marriage and divorce within legal boundaries, and both parties must accept this decision. There are detailed explanations of these issues in the subject of Islamic jurisprudence, as well as jurisprudential concepts that provide great clarity. These topics have been thoroughly discussed by renowned scholars. The opinions, evidence, and fatwas (religious rulings) of these experts are based on their school of thought. Syed Abul Aa'la Maudoodi has recently risen through the ranks of scholars. Time bears testament to his vision. Their attitudes on marriage and divorce are universal. Because all of his works, replies to inquiries, and constants have been considered. Domestic concerns, particularly marriage and divorce, will come to the fore with the advise of the Imams and Sidabula Ali Maududi.This is covered in further depth below.